Analisis Web Series dalam Format Film Pendek (Studi Kasus Web Series 'Malam Minggu Miko Episode Nissa') - Iqbal Alfajri; Irfansyah Irfansyah; Budi Isdianto (Wimba : Jurnal Komunikasi Visual, 2014)
A web series is a series of scripted videos, generally in episodic form, released on the Internet or also by mobile or cellular phone, and part of the newly emerging medium called web television. A single instance of a web series program is called an episode or webisode. This is an entertainment medium without a lot of history or precedent. As soon as one path to success is established, it quickly becomes obsolete and is replaced by additional innovations in the marketplace.Some web series shows are created by total amateurs, requiring little cost for equipment, special effects or anything else. Others are produced by businesses or bigger media networks, and there are a lot of them out there that are so good that they're comparable to real TV shows, especially if they involve well-known actors and professional directing or production.Web series creator posted new content on a consistent basis and built an audience of regular viewers. Berkala content is absolutely critical online. Successful online creators have had consistent content coming out on a regular schedule and creates a habit. More than any other medium, web series allow content creators to receive feedback from, interact with, their viewers almost instantaneously.Producing web series requires a blend of both independent film or short film and television techniques. Web series 'Malam Minggu Miko' is one of the web series produced in Indonesia that successfully uses the short film format to attract audiences adolescence. Web series also managed to become a pioneer in the use of the mockumentary approach as a story telling approach.